RETAK DAN KANDASNYA RUMAH TANGGA PASANGAN NIKAH KATOLIK DI WILAYAH MALUKU TENGGARA BARAT KEUSKUPAN AMBOINA - Ngutra, Seno; Seralarat, Kornelis (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2017)
Man and women are called to build their marriage in the world. It means that God is the main Creator of marriage. The marriage will be a sacrament because it shows to world a wonderful relationship between Christ, the head of the Church and His Body, which is the Church.” In one hand, the Church always strengthens her people to live harmoniously in their marriage, but the other hand, the Church facilatates those who have problem in their marriage to get an annulment. Annulment is a legal procedur for declaring  a marriage null an avoid. Unlike divorce, it is usually retroactive, meaning that an annulled  marriage is considered to be invalid from the begining almost as if it had never taken place.